Probing Ligand-binding Pockets of the Mevalonate Pathway Enzymes from Streptococcus pneumoniae - Lefurgy, Scott T. (American Society for Biochemistry and Molecular Biology, 2010)
Diphosphomevalonate (Mev·pp) is the founding member of a new class of potential antibiotics targeting the Streptococcus pneumoniae mevalonate (Mev) pathway. We have synthesized a series of Mev·pp analogues designed to simultaneously block two steps in this pathway, through allosteric inhibition of mevalonate kinase (MK) and, for five of the analogues, by mechanism-based inactivation of diphosphomevalonate decarboxylase (DPM-DC). The analogue series expands the C(3)-methyl group of Mev·pp with hydrocarbons of varying size, shape, and chemical and physical properties. Previously, we established the feasibility of a prodrug strategy in which unphosphorylated Mev analogues could be enzymatically converted to the active Mev·pp forms by the endogenous MK and phosphomevalonate kinase. We now report the kinetic parameters for the turnover of non-, mono-, and diphosphorylated analogues as substrates and inhibitors of the three mevalonate pathway enzymes. The inhibition of MK by Mev·pp analogues revealed that the allosteric site is selective for compact, electron-rich C(3)-subsitutents. The lack of reactivity of analogues with DPM-DC provided evidence, counter to the existing model, for a decarboxylation transition state that is concerted rather than dissociative. The Mev pathway is composed of three structurally and functionally conserved enzymes that catalyze consecutive steps in a metabolic pathway. The current work reveals that these enzymes exhibit significant differences in specificity toward R-group substitution at C(3) and that these patterns are explained well by changes in the volume of the C(3) R-group-binding pockets of the enzymes.